Factors influencing the public health emergency preparedness among Generation Z nursing interns in the post-pandemic era: a cross-sectional study - Duan, Chengxu; Feng, Guangyi; Zhuang, Xinqi; Zhou, Yenong; Jia, Yitong; Sun, Xiaomin; Zhang, Yin-Ping (Frontiers in Public Health, 2025)
BackgroundThe frequent occurrence of public health emergencies in the 21st century has posed significant challenges to global healthcare systems. As crucial members of medical teams, Generation Z nursing interns play a pivotal role in emergency response. However, systematic assessments of preparedness encompassing emergency attitude, professional knowledge, operational skills, and comprehensive competencies among nursing interns remain unexplored.ObjectiveThis study aims to assess the public health emergency preparedness of Generation Z nursing interns in the post-pandemic era and identify key influencing factors, providing insights for optimizing nursing education and clinical training.MethodsA cross-sectional survey was conducted among 434 Generation Z nursing interns in Zhengzhou, China, from January to February 2025 using convenience sampling. Data were collected using a general information questionnaire, Public Health Emergency Preparedness Questionnaire for Nursing Interns, Nurse's Digital Competence Self-assessment Scale, and Professional Identity Scale for Nursing Students. Data were analyzed by descriptive statistics, univariate analysis, Pearson's correlation, and multiple stepwise regression.ResultsThe total score of public health emergency preparedness of 434 nursing interns was 95.79 ± 11.03, with notable deficiencies in professional knowledge and comprehensive competencies. Multiple stepwise regression analysis revealed that digital competence, professional identity, attitude toward the nursing major, and level of internship hospital were the main influencing factors of emergency preparedness (all p < 0.05).ConclusionThe findings indicate that while Generation Z nursing interns demonstrate a high proficiency in emergency operations and a positive attitude toward emergency response, deficiencies persist in specialized emergency knowledge and psychological intervention capabilities. It is recommended that nursing schools and internship hospitals implement integrated emergency training programs, complemented by enhanced digital competency and professional identity cultivation, to holistically bolster preparedness for future public health emergencies.